Persepsi Masyarakat terhadap Konflik Manusia dan Gajah Sumatra (Elephas maximus sumatranus Temminck 1847) di Taman Nasional Way Kambas (Community Perception on the Conflict between Human and Sumatran Elephant (Elephas maximus sumatranus Temminck 1847) in Way Kambas National Park) - Pratiwi, Popy; Rahayu, Putri Sri; Rizaldi, Ahmad; Iswandaru, Dian; Winarno, Gunardi Djoko (Department of Forestry, Faculty of Agriculture, University of Lampung, 2020)
The conflict between humans and elephants can cause disadvantages for both humans and elephants in the form of property and loss of life. The objective of this study was to determine community perceptions of the conflict between humans and elephants. Data were collected through interviews with thirty respondents by using a questionnaire as guidance. The respondents were randomly selected from Tegal Yoso Village, Purbolinggo District, East Lampung Regency, which is one of the buffer villages of the Way Kambas National Park (TNWK). The results showed that 100% of the community declared elephants as plant destroyers, and 97% of plant consumers. The results also revealed that 100% of the community has a positive perception by considering elephants as an endangered species and has the potential to become tourist attractions, while 97% or the community considered elephant as a charismatic animal, beautiful, having a strong memory, and sensitive. The community showed awareness of the conservation of Sumatran elephants. It was shown from their attitude in dealing with the elephants that enter the agricultural area by reporting to the authorized officer. The Elephant Response Unit (ERU) in Tegal Yoso and the community need to increase safeguards to reduce conflicts between elephants and humans in the buffer zone of TNWK. Keywords: elephant, community, conflict, mitigation, perception